Oppositions and Their Member Nominations in the Conflict Communication Discourse of Artūras Paulauskas (2004) - Linkevičiūtė, Vilma (Verbum, 2013)
The object of this article is the linguistic means of political conflict communication that are characteristic of the political discourse of the Acting President of Lithuania Artūras Paulauskas (2004). Conflict communication has become a research object of modern conflictology, which mainly focuses on interpersonal conflict and effective methods of managing conflict solutions. Political conflict communication, which is generally analysed on the basis of parliamentary debates, does not have a precise definition. Conflict communication can be defined as verbalizing conflict situations, which are conditioned by variances with set objectives or their means of implementation and by discrepancies between the interests and wishes of the sides involved in the conflict. In political communication, it is possible to talk about the fact that an initial situation of verbal and non-verbal actions can become a source of conflict, while disapproval of such a situation is verbalized in political communication. Any individual who wants to influence political events becomes the subject of such communication.